Structural Divergence of the Group I Intron Binding Surface in Fungal Mitochondrial Tyrosyl-tRNA Synthetases That Function in RNA Splicing - Lamech, Lilian T. (J Biol Chem, 2016)
The mitochondrial tyrosyl-tRNA synthetases (mtTyrRSs) of Pezizomycotina fungi, a subphylum that includes many pathogenic species, are bifunctional proteins that both charge mitochondrial tRNA(Tyr) and act as splicing cofactors for autocatalytic group I introns. Previous studies showed that one of these proteins, Neurospora crassa CYT-18, binds group I introns by using both its N-terminal catalytic and C-terminal anticodon binding domains and that the catalytic domain uses a newly evolved group I intron binding surface that includes an N-terminal extension and two small insertions (insertions 1 and 2) with distinctive features not found in non-splicing mtTyrRSs. To explore how this RNA binding surface diverged to accommodate different group I introns in other Pezizomycotina fungi, we determined x-ray crystal structures of C-terminally truncated Aspergillus nidulans and Coccidioides posadasii mtTyrRSs. Comparisons with previous N. crassa CYT-18 structures and a structural model of the Aspergillus fumigatus mtTyrRS showed that the overall topology of the group I intron binding surface is conserved but with variations in key intron binding regions, particularly the Pezizomycotina-specific insertions. These insertions, which arose by expansion of flexible termini or internal loops, show greater variation in structure and amino acids potentially involved in group I intron binding than do neighboring protein core regions, which also function in intron binding but may be more constrained to preserve mtTyrRS activity. Our results suggest a structural basis for the intron specificity of different Pezizomycotina mtTyrRSs, highlight flexible terminal and loop regions as major sites for enzyme diversification, and identify targets for therapeutic intervention by disrupting an essential RNA-protein interaction in pathogenic fungi.